Visual taxonomies and lines research from visual culture - Rocha Jiménez, Darío Roque (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
This paper talks about classifying and presenting research lines, in terms of visual culture in direct co dependence with art research, along with some discussions on the nature of creative emergencies in the cultural and arts fields. This contribution, different from the analysis of philosophical semiotic-linguistic discourses or aesthetic decoding, is made from elements of the same art practices, as "a map" to explore in conjunction with visual studies and visual arts.